Personal Digital Assistants (PDAs) in Pediatrics & Paediatric Critical Care Websites - Vidhyashankar, C (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> doi:10.3126/jnps.v27i2.1590 J. Nepal Paediatr. Soc. Vol.27(2) p.95-96